The Effects Of Periodontal Therapy On Biochemical Inflammatory Markers On Renal Dysfunction Patients - Cerasela Sincar; Sorina Solomon; Ioana Rudnic; Ioana Martu; Silvia Martu (Romanian Society of Oral Rehabilitation, 2013)
Introduction Recent studies have shown an association between high levels of C-Reactive Protein (CRP), Interleukin-6 (IL-6) and chronic periodontitis, association which is diminished after the periodontal treatment. Due to this association, chronic periodontitis was recently considered as a risk factor for chronic kidney disease. The aim of the study The purpose of this study was to demonstrate that the inflammatory chronic response observed on patients with chronic kidney disease is influenced by the chronic periodontitis that induces high levels of expression of inflammatory markers, such as IL-6 and CRP. Materials and methods The patients in the study were divided in two groups (a group of patients with CKD that were submitted to conservative periodontal treatment and a control group of patients without any systemic disease with moderate to severe chronic periodontitis). The periodontal therapy included root planning and debridement. After the periodontal treatment completion the patients were recalled at 15, 30, 60 and 90 days. We determined the levels of IL-6 and CRP initially and at 3 months after therapy. Results IL-6 and CRP levels have significantly decreased after the periodontal treatment in both groups. Additionally, significantly higher levels of haemoglobin and ferritin were observed in the control group patients, associated with the periodontal treatment. Conclusions Our results demonstrate that chronic periodontitis is more severe on chronic kidney disease patients, inducing a systemic inflammatory response. The periodontal therapy reduces the inflammatory component and decreases the levels of the serum markers, indicating an important interventional therapy on patients with chronic kidney disease.